Frog music : a novel - Donoghue, Emma, 1969- (Little, Brown and Company, 2014)
"Summer of 1876: San Francisco is in the fierce grip of a record-breaking heatwave and a smallpox epidemic. Through the window of a railroad saloon, a young woman called Jenny Bonnet is shot dead. The survivor, her friend Blanche Beunon, is a French burlesque dancer. Over the next three days, she will risk everything to bring Jenny's murderer to justice--if he doesn't track her down first. The story Blanche struggles to piece together is one of free-love bohemians, desperate paupers and arrogant millionaires; of jealous men, icy women and damaged children. It's the secret life of Jenny herself, a notorious character who breaks the law every morning by getting dressed: a charmer as slippery as the frogs she hunts. In thrilling, cinematic style, FROG MUSIC digs up a long-forgotten, never-solved crime. Full of songs that migrated across the world, Emma Donoghue's lyrical tale of love and bloodshed among lowlifes captures the pulse of a boomtown like no other"--